Analysis of Consumer Satisfaction Levels with Bulog Rice in the Cheap Food Movement (GPM) Program in Binjai City: English - Wulandari, Suci; Musika Lubis, Mitra (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
The purpose of this research is to determine the level of consumer satisfaction with Bulog rice in the Cheap Food Movement (GPM) program in the city of Binjai. In this research, the method used is a case study approach, utilizing tools such as Importance-Performance Analysis (IPA) and Customer Satisfaction Index. (CSI). The sample size for this study is 30 respondents using the convenience sampling technique. The characteristics for sample collection are as follows: 1.) Bring an ID card with a Binjai address, 2.) and purchase a minimum of 1 package and a maximum of 3 packages of Bulog products in the Cheap Food Movement (GPM) program in Binjai City. The results of this study indicate that, based on the analysis of Importance-Performance (IPA), attributes found in quadrant I (maximum priority) such as the soft texture of the rice, the bright white color of the rice, and the affordable price offered at Rp.55,000/5kg are the main priorities for consumer satisfaction. Additionally, according to the calculation of the Customer Satisfaction Index (CSI), a value of 87.715 was obtained, which falls within the range of > 81%. This indicates that consumers are satisfied with the purchase of Bulog rice in the city of Binjai as part of the Affordable Food Movement program in Binjai.